Local Government Strategies in Preventing Child Marriage: A Study of the Women’s Empowerment and Child Protection Office of Sinjai Regency - Mulawangsa, A; Jusni; Jamaluddin (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2025)
This study aims to analyze the strategy of the Women’s Empowerment and Child Protection Office (DP3AP2KB) of Sinjai Regency in reducing the incidence of child marriage. The research employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation involving key informants, including the Head of DP3AP2KB, the Head of the Child Protection Division, the Head of the Office of Religious Affairs, and community representatives. Data analysis was conducted using thematic procedures consisting of data reduction, data display, and conclusion drawing. The findings indicate that the main strategies implemented include the establishment of Community-Based Integrated Child Protection (PATBM), periodic monitoring and evaluation, and intensified socialization regarding the risks of child marriage and the importance of child rights protection. Nevertheless, the implementation still encounters obstacles, particularly low public awareness and the uneven establishment of PATBM across villages. The novelty of this study lies in the comprehensive mapping of child marriage prevention strategies by emphasizing cross-sectoral collaboration and structured monitoring mechanisms. These findings imply that strengthening village-level institutions, expanding PATBM coverage, and enhancing community-based educational programs are crucial to achieving more effective and sustainable child marriage prevention in Sinjai Regency.